Learner Behavior Analysis on an Online Learning Platform - El Haddioui, Ismail; Khaldi, Mohamed (International Journal of Emerging Technologies in Learning (iJET), 2012)
This paper introduces the study of the learners’ behavior on e-learning platform to create profiles that regroup learners according to their behavior on the platform. This system can be used by the learner-agent of an intelligent tutoring system (ITS). Thus, this system will allow us to better understand the learner in a virtual learning environment to improve the learning situation by placing the learner at the center of the learning process.